THE INFLUENCE OF SEDIMENTATION AND POST-SEDIMENTATION TRANSFORMATIONS ON THE RESERVOIR PROPERTIES OF THE ROCKS - Khomyn, V.; Мaniuk, M.; Maniuk, O.; Popluiko, A.; Khovanets, N. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The topicality of the research is proved by the scientific evidence of the peculiarities of the sedimentation and post-sedimentation transformations of the rocks in relation to their possible oil and gas content. The productive sediments of the deposits of the interior of the Precarpathian Depression were thoroughly and lithologically researched. The objective implied the study and recognition of the reservoir properties within primary (sedimentation) and secondary (post-sedimentation) factors. The primary ones are as follows: granulity (grains median diameter), sorting, and rock maturity. Consequently, a positive correlation between the grains median diameter and rock porosity has been determined; the very coefficient equals 0.56. Evidently, unlike the well-sorted sandstones, the badly graded ones are marked by poor porosity and permeability. The positive correlation between porosity and clastic quartz content is revealed: should the latter increase, the former will go up as well. Apparently, more mature sandstones are characterized by dramatically high porosity; this factor positively affects the reservoir properties of the rocks. After studying the secondary transformations of the sandy rocks, we have determined that the diagenesis stage is defined by the change of mineral composition. This alteration is mainly caused by organic material decomposition and the appearance of reducing environment. Considering the cover thickness, we have graded the transformations of the fragments of the sandy-aleuritic rocks of the depression. The pattern of the catagenetic changes at various depths has been introduced. In the end, we have inferred that the increasing depth starts influencing the three types of the structures, i.e. incorporating, reclaiming and microstilolite rather gradually. In addition, the declining importance of the conformal structures has been identified. The stress pattern of the catagenetically transformed solid rocks promotes the microfracture within the late catagenesis zones; this factor predetermines the development of decompression zones at the depths exceeding 4 km characterised by good reservoir properties.
Keywords: reservoir properties; porosity; permeability; correlations